2011
DOI: 10.1021/mp200194s
|View full text |Cite
|
Sign up to set email alerts
|

Purified Herpes Simplex Type 1 Glycoprotein D (gD) Genetically Fused with the Type 16 Human Papillomavirus E7 Oncoprotein Enhances Antigen-Specific CD8+ T Cell Responses and Confers Protective Antitumor Immunity

Abstract: Type 1 herpes virus (HSV-1) glycoprotein D (gD) enhances antigen-specific immune responses, particularly CD8(+) T cell responses, in mice immunized with DNA vaccines encoding hybrid proteins genetically fused with the target antigen at a site near the C-terminal end. These effects are attributed to the interaction of gD with the herpes virus entry mediator (HVEM) and the concomitant blockade of a coinhibitory mechanism mediated by the B- and T-lymphocyte attenuator (BTLA). However, questions concerning the req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 38 publications
1
25
0
11
Order By: Relevance
“…Previous results, based both on DNA vaccines and adenovirus vectors, have demonstrated that the fusion of heterologous sequences at the C-terminus of gD target the protein to the outer face of the cytoplasmic membrane where the binding to HVEM occurs, leading to the enhanced activation of CD8 + T cell responses to the heterologous antigen [13], [15], [32], [36]. Similar but less significant results have also been obtained with recombinant purified proteins [14], further suggesting that endogenous expression and membrane localization contributes to the gD-mediated CD8 + T cell adjuvant effects.…”
Section: Discussionmentioning
confidence: 64%
“…Previous results, based both on DNA vaccines and adenovirus vectors, have demonstrated that the fusion of heterologous sequences at the C-terminus of gD target the protein to the outer face of the cytoplasmic membrane where the binding to HVEM occurs, leading to the enhanced activation of CD8 + T cell responses to the heterologous antigen [13], [15], [32], [36]. Similar but less significant results have also been obtained with recombinant purified proteins [14], further suggesting that endogenous expression and membrane localization contributes to the gD-mediated CD8 + T cell adjuvant effects.…”
Section: Discussionmentioning
confidence: 64%
“…The gD, gDE7, and E7 recombinant proteins were expressed and purified as previously described (12). The concentration and the integrity of the antigens were routinely checked by PAGE and the molecular weights corresponded to those predicted in silico.…”
Section: Antigens and Immunizationsmentioning
confidence: 99%
“…In this scenario, our group has developed two therapeutic vaccine strategies to control HPV-16-associated tumors based either on naked DNA (11) or on purified recombinant protein (12). Both strategies are based on the expression of a hybrid protein generated after the genetic fusion of HSV-1 gD with HPV-16 E7 oncoprotein (gDE7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, herpes simplex virus infection may be an independent risk factor for vulvar cancer. Some studies have found that patients with vulvar cancer have a high positive rate of herpes simplex virus II in serum and genital herpes infection [7].…”
Section: Introductionmentioning
confidence: 99%